Cognitive assessment of dyslexic students in higher education - Hatcher, J; Snowling, M; Griffiths, Y (2002)
Background. Previous studies have shown that the phonological deficits that characterise dyslexia persist into adulthood. There is a growing number of dyslexic students in higher education for whom sensitive diagnostic tests of their reading and reading related difficulties are required. Aims. The main aim of this study was to compare the cognitive skills of dyslexic students with those of their non-dyslexic peers, and to ascertain the impact of cognitive difficulties on their study skills. A second aim was to produce guidelines for the assessment of dyslexia in higher education. Sample. The performance of 23 dyslexic students was compared with that of a comparison group of 50 students from the same university who did not report a history of reading difficulty. Method. Participants completed standardised tests of IQ, reading, spelling and arithmetic and tests tapping phonological processing, verbal fluency and speed of processing. Their performance on a set of study-related tasks including proof reading and précis writing was also assessed and they completed the Brown ADD scales. Results. Although dyslexic students did not differ in general cognitive ability from controls, they had deficits in reading and reading related phonological processes. Discriminant function analyses indicated that dyslexia in adulthood can be confirmed with 95% accuracy using only four tests: spelling, nonword reading, digit span and writing speed. Conclusions. The study highlighted the difficulties of dyslexic adults. The persisting difficulties of dyslexic students that affect their study skills need to be recognised by HE institutions so that appropriate support programmes can be put in place.